Induction of oxidative damage in the testes and spermatozoa and hematotoxicity in rats exposed to multiple doses of ethylene glycol monoethyl ether (2010)
The effects of ethylene glycol monoethyl ether (EGEE) on the antioxidant systems of the testes and epididymal spermatozoa were investigated in rats at dose levels of 0, 100, 200 and 400 mg kg–1 body weight (bw) administered orally by gavage for 14 consecutive days. The bw gain of the EGEE-treated rats decreased significantly at 200 and 400 mg kg–1 bw compared with the control group. There were no significant changes in the weights of the testes, epididymis, seminal vesicles and prostate glands of the EGEE-treated rats. In the testes, while EGEE treatment resulted in significant decrease in glutathione (GSH) level, superoxide dismutase (SOD) and catalase (CAT) activities, it markedly increased the malondialdehyde (MDA) level, glutathione-S-transferase (GST) and lactate dehydrogenase (LDH) activities at 200 and 400 mg kg–1 dose levels but vitamin C content remained unaffected in all the groups. In the spermatozoa, administration of EGEE caused significant decrease in the activities of CAT, GST and LDH as well as in the levels of vitamin C and GSH but significantly increased the MDA level and SOD activity compared with the control rats. Histopathological examination showed severe degeneration of the testes, such as generalized erosion and necrosis of the germinal epithelium of the